Training Needs Analysis in a Government Regulatory Firm (B). Issue 1 (March 2018) - Karve, Shailaja; Aggarwal-Gupta, Meenakshi
Western State Electricity Regulatory Commission (WSERC) a Government Regulatory Firm in India needed to enhance its human resource capabilities. It was grappling with employees who were either on contract or deputation, and were essentially temporary in nature. The younger staff was lacking in both technical and managerial skills and could not contribute to the organization's functioning. The senior staff appeared unwilling to transfer their knowledge to the junior staff. In addition, there were various people-related challenges in terms of differences in working styles, hierarchical culture of the firm, conflict across levels and functions and preference to operate in silos. It was decided to address the people related challenges through training to create a climate of trust and sharing before initiating a mentoring intervention. It was decided to undertake customized training to address the unique context and challenges being faced by the firm; therefore, a training needs analysis (TNA) was carried out. Various tools such as the TNA questionnaire, visioning exercise, personal interviews and focused group discussions (FGD) were used to gather data to identify specific training needs of the firm. The case focuses on the process of initiating a TNA in a small firm and some of the associated challenges.